MSC-EVs transferring mitochondria and related components: A new hope for the treatment of kidney disease - Mao, Jueyi; Li, Cuifang; Wu, Feifeng; She, Zhou; Luo, Senlin; Chen, Xiaoyu; Wen, Chuan; Tian, Jidong (Frontiers in Immunology, 2022)
Kidney disease is a serious hazard to human health. Acute or chronic renal disease will have a significant negative impact on the body’s metabolism. The involvement of mitochondria in renal illness has received a lot of interest as research on kidney disease has advanced. Extracellular vesicles are gaining popularity as a means of intercellular communication in recent years. They have a close connection to both the nephropathy process and the intercellular transfer of mitochondria. The goal of this review is to present the extracellular vesicle transport mitochondria and its related biologically active molecules as new therapeutic options for the treatment of clinical kidney disease. This review focuses on the extracellular vesicles through the transfer of mitochondria and its related bioactive molecules, which affect mitochondrial energy metabolism, take part in immune regulation, and secrete outside the body.